The prisoner of Zenda - Hope, Anthony (Nxb. Đồng Nai, 2009)
The hero of this classic swashbuckling romance, English gentleman Rudolf Rassendyll, is transported from a comfortable life in London to extraordinary adventures in Ruritania, a mythical land. Rassendyll bears an uncanny resemblance to Rudolf Elphberg, who is about to be crowned King of Ruritania; and when Elphberg's rival, the villainous Black Michael of Strelsau, attempts to seize power, Rassendyll impersonates the King to uphold the rightful sovereignty and ensure political stability. The redoubtable Rassendyll endures a trial of strength in his encounters with the infamous Rupert of Hentzau, and a quite different test as he grows to love the Princess Flavia.